Asuhan Keperawatan pada Pasien dengan Gangguan Sistem Persyarafan: Vertigo di Ruang Mawar 1 RSUD Dr. Soeselo Kabupaten Tegal - Hella Maulida Afrilliani; Titis Wening Setyoharsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Vertigo is a balance disorder that causes nausea, dizziness, and a spinning sensation. The purpose of this study is to ascertain how complete nursing care is implemented for a patient in the mawar 1 ward of RSUD dr. Soeselo Tegal Regency, who is suffering from vertigo, a nervous system condition. Observation, interviews, and documentation study techniques were employed in this investigation. According to the evaluation results, the patient had three nursing issues: nausea due to elevated intracranial pressure, reduced comfort due to disease symptoms, and knowledge deficiency due to insufficient information. Health education, ginger decoction to ease nausea, and the non-pharmacological brandt-daroff exercise technique to lessen vertigo symptoms were among the interventions. The assessment revealed that the patient's health had improved, as evidenced by a drop in the pain scale from a 5 to a 2, less nausea, and a better comprehension of the illness. In conclusion, it has been demonstrated that nursing care that combines pharmaceutical and non-pharmacological interventions like the brandt-daroff technique improves vertigo patients' conditions.